PERLINDUNGAN KONSUMEN PANGAN REKAYASA GENETIKA: RASIONALITAS DAN PROSPEK - Efendi, A'an; Ochtorina Susanti, Dyah; Kumala Sari, Nuzulia (Faculty of Law, Parahyangan Catholic University, 2022)
As a general observation we can say that there exists imbalance of power between producers and consumers of genetically engineered food. This paper, using a doctrinal legal approach, examines three issues: 1) the rationality of protecting consumers of genetically engineered food, 2) the rights of consumers of genetically engineered food, and 3) the effectiveness of consumer protection for genetically engineered food. Arguably, the same situation exists between producers and consumers of genetically engineered food. Disparities and power imbalance relating to knowledge, capital – or simply power – determines the answer to those questions above.